In vitro chemosensitivity of a canine tumor venereal transmissible cancer cell line - Franco Molina, Moisés Armides; Santamaría-Martínez, Edson Antonio; Santana Krimskaya, Silvia Elena; Zarate-Triviño, Diana Ginette; Kawas, Jorge R.; Ramos Zayas, Yareellys; Palacios Estrada, Natanael; Prado García, Heriberto; García Coronado, Paola Leonor; Rodríguez Padilla, Cristina (Frontiers in Veterinary Science, 2022)
The canine transmissible venereal tumor (CTVT) is the most common malignity in dogs. Because there are reports that this tumor is resistant to vincristine sulfate, the chemotherapeutic options are scarce, and the development of new therapeutic approaches is necessary. In this study, we evaluated the cytotoxic activity of vincristine, doxorubicin, temozolomide, panobinostat, toceranib, gemcitabine, cisplatin, fluorouracil, cyclophosphamide, and methotrexate on a CTVT cell line, determining that all drugs decreased the viability in a dose-dependent manner. Furthermore, they inhibit cellular migration in a time- and drug-dependent manner, as evaluated by the wound healing assay. On the other hand, vincristine, panobinostat, gemcitabine, toceranib, cyclophosphamide, and methotrexate increased the percentage of cells in the subG1 phase, and doxorubicin, temozolomide, gemcitabine, toceranib, and methotrexate decreased the percentage of cells in the synthesis phase. To efficientize the use of vincristine, only toceranib increased the cytotoxic effect of vincristine in a synergistic manner. Our results confirm the use of vincristine as the gold standard for CTVT treatment as monotherapy and suggest the use of a combinatorial and sequential treatment with toceranib.